Determinantes da sobrevivência de contratos de garantia de operações crédito no Paraná - Souza, Samya Letycia (2021)
The granting of microcredits to individuals and micro and small companies plays an important role in the maintenance and development of businesses, as well as in the generation of employment and income. However, the credit market has difficulties in meeting this type of organization due to the perception of risk of loss given the default. With the objective of minimizing the restrictions arising from such risk, mutual guarantee funds formalize and make the guarantee available só that micro and small companies and individuals have access to credit with favorable conditions. Given the granting of a guarantee, the funds are exposed to the risk that is directly associated with the maturity of the guaranteed credit agreements. The present research aimed to identify the determinants of the survival of credit agreements in guarantee operations, which are: fiscal type, sector, size and whether or not there is information on the number of employees. In addition, the survival curve of the contracts was estimated, identifying that 63.1% are likely to present the event in the 40 months of loans, which can facilitate the management of default and insolvency of companies throughout the life of the loan. Contract. For that, survival risk models and time until the event of microcredit contracts of a mutual guarantee fund in Paraná were estimated, using survival models with proportional risks with cure fraction. Based on these methods, it was possible to provide more information to assist in the management, quality of the portfolios and the efficiency of the guarantee fund’s credit operations.